The Role of Social Media in Campaigning the Danger of Drugs on Tiktok Account @infobnn_kabkuningan - Fida Kamal Fadhillah; Farida Nurfalah; Abdul Jalil Hermawan (Publikasi Indonesia, 2025)
Narcotics and dangerous substances are referred to as drugs. Napza, which stands for narcotics, psychotropic substances, and addictive substances, is another acronym introduced by the Ministry of Health of the Republic of Indonesia. The purpose of this study is to determine the role of Tiktok social media @infobnn_kabkuningan in conducting a drug hazard campaign, as well as explaining the strategies used in the drug hazard campaign and knowing how the audience responds to this drug hazard campaign. BNNK Kuningan in conducting a campaign for the Prevention, Eradication, Abuse and Illicit Trafficking of Drugs (P4GN). One of the methods used is social media. The social media used by The Kuningan National Narcotics Agency (BNNK) is the TikTok platform, the process of using the TikTok platform to disseminate P4GN information is by creating content related to drugs and adjusted to viral trends. The drug campaign carried out by BNNK Kuningan is more directed at providing information through social media with an approach that adjusts trends and audiences. Although it cannot be measured directly, the information conveyed is still considered valuable to the community. The main obstacles in this campaign are limited budget, personnel, and minimal audience involvement.